2022
DOI: 10.1038/s41598-022-15011-1
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of gestational malaria and maternal–neonatal outcomes, in Northwestern Colombia 2009–2020

Abstract: Research on Gestational Malaria (GM) is scarce in America's. In the few available studies in Colombia, the analysis of immunological or parasitological aspects predominates, with few analyzes of epidemiological aspects. The objectives were to determine the frequency of GM and submicroscopic infections (positive with PCR and negative with thick blood smears), to identify obstetric and malaria history associated with GM, and to describe maternal and neonatal outcomes associated with GM, in northwestern Colombia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
3
0
4
Order By: Relevance
“…Penelitian sebelumnya melaporkan outcome dari kehamilan dengan infeksi malaria paling banyak adalah anemia (32,1%), abortus (15,5%), neonatal malaria (15,5%), berat badan lahir rendah (6,5%), lahir mati (2,5%), dan kematian janin (1%). 10 Banyaknya dampak buruk akibat infeksi malaria selama kehamilan, maka perlu adanya perhatian khusus untuk mencegah dan mengurangi prevalensi malaria pada ibu hamil. Masih kurangnya informasi terkait patobiologi terkait infeksi malaria pada ibu hamil yang menyebabkan strategi pencegahan dan terapi belum optimal.…”
Section: Pendahuluanunclassified
See 3 more Smart Citations
“…Penelitian sebelumnya melaporkan outcome dari kehamilan dengan infeksi malaria paling banyak adalah anemia (32,1%), abortus (15,5%), neonatal malaria (15,5%), berat badan lahir rendah (6,5%), lahir mati (2,5%), dan kematian janin (1%). 10 Banyaknya dampak buruk akibat infeksi malaria selama kehamilan, maka perlu adanya perhatian khusus untuk mencegah dan mengurangi prevalensi malaria pada ibu hamil. Masih kurangnya informasi terkait patobiologi terkait infeksi malaria pada ibu hamil yang menyebabkan strategi pencegahan dan terapi belum optimal.…”
Section: Pendahuluanunclassified
“…Beberapa hasil penelitian menunjukkan bahwa ibu hamil dengan infeksi malaria lebih berisiko untuk terjadinya kelahiran prematur, anemia berat, kematian janin dalam rahim, dan keguguran. 10,22 Dampak lainnya terhadap bayi diantaranya BBLR, lahir mati, dan kematian neonatus. 22,23…”
Section: Dampak Infeksi Malaria Pada Maternal Dan Neonatalunclassified
See 2 more Smart Citations
“…A meta-analysis reported a prevalence of 16.7% (95% confidence interval [CI], 9.0–28.8) for GM, 11.0% (95% CI, 4.1–26.3) PM, and 16.2% (95% CI, 8.2–29.5) CM [ 13 ]. Another study found 35.8% GM, associated with maternal anemia, CM, and lower birth weight [ 14 ]. A study reported PM 27.7%, associated with CM, lower neonatal weight, and maternal anemia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%